PENGEMBANGAN KARIR, KOMPETENSI, KEPEMIMPINAN, KOMITMEN ORGANISASIONAL DAN KINERJA - Kiswanto, Ivandeza Putra, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Career Development, Competence, Leadership, Organizational Commitment and Performance. The purpose of this study was to determine the effect of career development, competence and leadership on employee performance with organizational commitment as an intervening variable in the Department of Industry and Trade of Riau Province. This study uses primary data using questionnaires, then processed by the path analysis method. The population is all employees of Industry and Trade in Riau Province as many as 220 people and samples taken 142 using Slovin formula. The results of this study are that competence and leadership statistically significantly affect organizational commitment. However, there is no significant relationship between career development and organizational commitment. Competence and leadership are statistically significant in influencing performance while career development and organizational commitment do not exist.